V7/N1 Editorial - Bengtsen, Peter (SAUC - Street Art and Urban Creativity (repository), 2021)
Since 2015, six issues of the journal Street Art and Urban Creativity have been published, with a total of 84 research articles and numerous essays, working papers and book reviews. The journal, along with the annual Urban Creativity conference in Lisbon and a number of other publications and activities – including the research network Urban Creativity Lund – are indications that the field of urban creativity studies has become increasingly established. The field of urban creativity studies has a broad range of interests including, but not limited to, street art, graffiti, urban foraging, parkour, skateboarding and guerrilla gardening. However, as with any field, once it starts to settle, a dominant paradigm tends to emerge. This will to some degree influence what is considered the core of the field, not only in terms of objects of study, but also in terms of method and theoretical approaches. As a part of this year’s call for submissions to the journal, in addition to our general call (see below), we invite contributions that reflect on the current status and the future of the transdisciplinary academic field of urban creativity studies that has emerged over the last two decades.